Novel multitarget analgesic candidate SZV-1287 demonstrates potential disease-modifying effects in the monoiodoacetate-induced osteoarthritis mouse model - Ádám István Horváth; Ádám István Horváth; Kata Bölcskei; Nikolett Szentes; Nikolett Szentes; Nikolett Szentes; Éva Borbély; Éva Borbély; Valéria Tékus; Valéria Tékus; Valéria Tékus; Bálint Botz; et al. (Frontiers in Pharmacology, 2024)
IntroductionMonoiodoacetate (MIA)-induced osteoarthritis (OA) is the most commonly used rodent model for testing anti-OA drug candidates. Herein, we investigated the effects of our patented multitarget drug candidate SZV-1287 (3-(4,5-diphenyl-1,3-oxazol-2-yl) propanal oxime) that is currently under clinical development for neuropathic pain and characterized the mouse model through complex functional, in vivo imaging, and morphological techniques.MethodsKnee OA was induced by intraarticular MIA injection (0.5 and 0.8 mg). Spontaneous pain was assessed based on weight distribution, referred pain by paw mechanonociception (esthesiometry), edema by caliper, neutrophil myeloperoxidase activity by luminescence, matrix metalloproteinase activity, vascular leakage and bone remodeling by fluorescence imaging, bone morphology by micro-CT, histopathological alterations by semiquantitative scoring, and glia activation by immunohistochemistry. Then, SZV-1287 (20 mg/kg/day) or its vehicle was injected intraperitoneally over a 21-day period.ResultsMIA induced remarkable weight bearing and paw withdrawal threshold decrease, alterations in the tibial and femoral structures (decreased trabeculation and cortical erosions), histopathological damage (disorganized cartilage structure, hypocellularity, decreased matrix staining, disrupted tidemark integrity, synovial hyperplasia, and osteophyte formation), and changes in the astrocyte and microglia density in the lumbar spinal cord.ConclusionSZV-1287 may have disease-modifying potential through analgesic, anti-inflammatory, and chondroprotective effects. The MIA mouse model is valuable for investigating OA-related mechanisms and testing compounds in mice at an optimal dose of 0.5 mg.